Direct electric current modifies important cellular aspects and ultrastructure features of Candida albicans yeasts: Influence of doses and polarities. Issue 2 (26th October 2016) - Barbosa, Gleyce Moreno; dos Santos, Eldio Gonçalves; Capella, Francielle Neves Carvalho; Homsani, Fortune; de Pointis Marçal, Carina; dos Santos Valle, Roberta; de Araújo Abi‐Chacra, Érika; Braga‐Silva, Lys Adriana; de Oliveira Sales, Marcelo Henrique; da Silva Neto, Inácio Domingos; da Veiga, Venicio Feo; dos Santos, André Luis Souza; et al.
Abstract : Available treatments against human fungal pathogens present high levels of resistance, motivating the development of new antifungal therapies. In this context, the present work aimed to analyze direct electric current (DC) antifungal action, using an in vitro apparatus equipped with platinum electrodes. Candida albicans yeast cells were submitted to three distinct conditions of DC treatment (anodic flow—AF; electroionic flow—EIF; and cathodic flow—CF), as well as different charges, ranging from 0.03 to 2.40 C. Our results indicated C. albicans presented distinct sensibility depending on the DC intensity and polarity applied. Both the colony‐forming unit assay and the cytometry flow with propidium iodide indicated a drastic reduction on cellular viability after AF treatment with 0.15 C, while CF‐ and EIF‐treated cells stayed alive when DC doses were increased up to 2.40 C. Additionally, transmission electron microscopy revealed important ultrastructural alterations in AF‐treated yeasts, including cell structure disorganization, ruptures in plasmatic membrane, and cytoplasmic rarefaction. This work emphasizes the importance of physical parameters (polarity and doses) in cellular damage, and brings new evidence for using electrotherapy to treat C. albicans pathology process. Bioelectromagnetics. 38:95–108, 2017. © 2016 Wiley Periodicals, Inc.